Assessing the nicotine content of smoked and smokeless forms of Tobacco Available in Bhopal - H V Amith; Deepali Agrawal; Abhishek Gupta; Tarani Prakash Shrivastava; Bharathi M Purohit; Garima Bhambhani (Wolters Kluwer Medknow Publications, 2018)
Context: Abuse of tobacco, such as drug and alcohol abuse, is a worldwide public health problem. Once a person is addicted to nicotine, quitting smoking is difficult. A measure of the addictive potential of tobacco products is the amount of nicotine available from them. The present study is an attempt to assess the nicotine content of tobacco products available in Bhopal. Aims: This study aims to assess the nicotine content of some popular brands of smoked (cigarettes and bidis) and chewed forms (pan masalas containing tobacco) of tobacco available in Bhopal. Settings and Design: This was an in vitro cross-sectional study. Subjects and Methods: Six brands of cigarettes (filtered), six brands of bidis, and six brands of chewed tobacco (pan masalas) were used for the study. The methodology published by Association of Official Analytical Chemists was followed, and reagents conforming to American Chemical Society specifications were used. Statistical Analysis Used: One-way ANOVA, Bonferroni post hoc test. Results: The mean nicotine levels for cigarettes, bidis, and chewed tobacco were 7.84 ± 5.10, 16.86 ± 5.66, and 16.30 ± 3.33, respectively. The differences in the mean scores were compared using one-way ANOVA and were found to be statistically significant with F = 6.636 and P = 0.009. Bonferroni post hoc test assessed the difference in mean nicotine content among the groups indicating that the difference between cigarettes versus bidis and cigarette versus chewed tobacco was significant with P = 0.016 and 0.024, respectively. Conclusions: Bidis had the highest content of nicotine, followed by chewed tobacco (pan masalas) and cigarettes.